Life cycle cost assessment of recycled paper manufacture in China. (10th April 2020) - Li, Jigeng; Mei, Mengyu; Han, Yulin; Hong, Mengna; Man, Yi
Abstract: Recovered paper is one of the major raw material for recycled papermaking industry. In China, the domestic recovered paper recycling system is incomplete and the amount of recyclable recovered paper cannot satisfy the papermaking demand. Therefore, the recycled papermaking industry is extremely dependent on imported recovered paper as their raw fiber source. In 2018, Chinese government announced a ban on unsorted recovered paper and tightened the import quota for recovered paper, which resulted in a dramatic drop in the importing amount of recovered paper. It is an urgent issue to explore alternative production routes that are more economical and environmentally friendly. Herein, life cycle cost assessment is used to compare and analyze the recycled papermaking industry based domestic recovered paper and three alternatives (including straw, imported deinked pulp and imported wood pulp) as the raw materials. The results show that the life cycle cost of domestic recycled paper based recovered papermaking is significantly lower than the other three alternatives, whereas its external cost is higher than that of the production routes based on the imported deinked pulp and imported wood pulp. With the increasing price of the domestic recovered paper, imported deinked pulp is the trend of recycled papermaking industry in China. Highlights: Life cycle cost assessment is applied to the recycled paper industry in China. LCC of four papermaking schemes based on different raw materials were assessed. LCC for six types of paper products ranges from 924 to 1227 USD/t in 2017. Imported recovered pulpboard is the best choice of wastepaper material supplement.